Measuring Sustainability Elements in PR1MA Affordable Housing - Azlina Md. Yassin; Masrom, Md. Asrul Nasid; Yahya, Mohd Yamani (International Journal of Sustainable Construction Engineering and Technology, 2022)
Housing has become a vital instrument in daily life, not because of the cost and functionâ€™s only but housing can provide other attributes of a feasible urban life. Thus, Malaysia’s government has struggled to cater affordable housing to counter economic concerns and adopt a sustainable housing development aspect for a better quality of life. However, even the housing affordability of low and middle-income earners has been improved, but some of them are remains in debating. The objective of this paper is to measure the sustainability element in PRIMA affordable projects in Malaysia as well as to determine the satisfaction level of sustainable affordable housing practice among PR1MA residents. The data were collected from 97 survey forms distributed amongst PR1MA residents through Google form and self-administered and were considered as useful data for further analysis. The results show that only social and environmental elements were determined as sustainability elements in PR1MA affordable housing in selected PR1MA projects in Malaysia. Moreover, the results revealed that majority respondents have low satisfaction level on economic sustainability in sustainable affordable housing practice within their residential area. Thus, this result has a significant contribution to the stakeholders who are directly or indirectly participated in affordable housing development and specifically PR1MA projects. This result also helps the policy makers and practitioner for emphasizing several important elements for developing affordable housing in future.